Implementation of finite difference method for detecting brain tumor growth - Nur Syazwani Mohd Nasir (Institute of Engineering Mathematics, Universiti Malaysia Perlis, 2017)
The main objective of this study is to detect the brain tumor growth. In order to achieve the main objective, the following sub-objectives will be carried out ; to discretize 1D reaction diffusion equation using explicit finite difference methods ; to develop numerical algorithms and procedures for solving 1D reaction diffusion equation ; to verify the accuracy of the selected finite difference method in predicting the growth of brain tumor.